Pengaruh Budaya Organisasi, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Bangunan Tangguh Makmur - Agus Johanes (LPPM Universitas Putera Batam, 2025)
In today's era, every company plays a crucial role in achieving its vision and mission, which is through Human Resources (HR). Therefore, to reach the company's goals, it is essential for each company to motivate its employees to continuously improve their performance and develop. This study aims to analyze the influence of organizational culture, work discipline, and work motivation on employee performance at PT Bangunan Tangguh Makmur. The research involves 110 respondents as the sample, using a non-probability sampling technique in the form of saturated sampling. Data were collected through the distribution of questionnaires, and data analysis was conducted through a series of quality tests, including validity tests, reliability tests, and classical assumption tests, such as normality tests, multicollinearity tests, and heteroscedasticity tests. To examine the effects between variables, multiple linear regression analysis and coefficient of determination analysis were used, while hypothesis testing was performed using the t-test. The results show that organizational culture, work discipline, and work motivation have a significant simultaneous effect on employee performance at PT Bangunan Tangguh Makmur.